2014
DOI: 10.1378/chest.13-2652
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Guidelines for VTE Risk Among Nursing Home Residents

Abstract: BACKGROUND:Nursing home (NH) residents are at increased risk for both VTE and bleeding from pharmacologic prophylaxis. Construction of prophylaxis guidelines is hampered by NHspecifi c limitations with VTE case identifi cation and characterization of risk. We addressed these limitations by merging detailed provider-linked Rochester Epidemiology Project (REP) medical records with Centers for Medicare and Medicaid Services Minimum Data Set (MDS) NH assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Reduced physical activity leads to stasis or slow blood flow, which in turn allows small clots to gradually fuse and form larger blood clots. Many studies have confirmed the relationship between long-term inactivity and DVT ( 16 - 19 ). In particular, Apenteng et al ’s prospective cohort study demonstrated that in the same population, the incidence of VTE was obviously higher in long-term bedridden people than in old people who were able to act on their own in care homes ( 17 ).…”
Section: Discussionmentioning
confidence: 94%
“…Reduced physical activity leads to stasis or slow blood flow, which in turn allows small clots to gradually fuse and form larger blood clots. Many studies have confirmed the relationship between long-term inactivity and DVT ( 16 - 19 ). In particular, Apenteng et al ’s prospective cohort study demonstrated that in the same population, the incidence of VTE was obviously higher in long-term bedridden people than in old people who were able to act on their own in care homes ( 17 ).…”
Section: Discussionmentioning
confidence: 94%
“…We previously investigated NHVTE risk factors and/or anticoagulant use using manual abstraction of REP medical records. [48,49] Our previous studies ascertained NHVTE among Olmsted County residents, using the same VTE case criteria employed in this study, and using CMS-MDS to obtain information on NH admissions for NHVTE cases and age-, sex-, calendar-year-matched NH non-VTE controls. Pharmacologic prophylaxis rates appeared higher for NH residents than for all elderly Olmsted County residents; among NH residents, the proportions receiving pharmacologic prophylaxis 3 months before index were 32% for non-VTE controls and 45% for VTE cases;[48] in our current longitudinal cohort study of NHVTE incidence, a slightly higher 54% of cases received pharmacologic prophylaxis within the 3 months before the incident NHVTE event, perhaps reflecting use of low molecular weight heparin (LMWH) in this later time period (17% of the 111 were treated with LMWH).…”
Section: Discussionmentioning
confidence: 99%
“…Additional NHVTE risk factors were identified in our two previous REP publications, the first employed REP medical record data alone,[48] the second combined REP medical record data with CMS-MDS data. [49] In the first study, NHVTE risk was significantly associated with active malignancy, recent hospitalization, and recent surgery. However, the prevalence of all evaluated VTE risk factors appeared much higher in NH controls than in general population controls, thus the magnitude of risk appeared much lower than for general population estimates (e.g., odds ratio for major surgery = 2.5 [95% CI=1.4–4.3] for NH residents vs 11 [95% CI=7.0–17] for the general population).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, current guidelines provide no specific recommendations for thromboprophylaxis in the nursing home setting 3 . This is likely the case because in‐hospital studies cannot be readily used to extrapolate to the nursing home population, due to distinct risk factors for VTE in the nursing home population such as dependency in activities of daily living (ADL), wheelchair use, and frequent/prolonged immobilization 5,8 . Alternatively, there exists an incremental increase of bleeding risk in this vulnerable population based on individual risk factors such as falls, dementia, use of non‐steroidal anti‐inflammatory drugs, and/or renal failure to make a balanced decision on the use of thromboprophylaxis.…”
Section: References Population (Sample Size) Study Type/design Age (Y...mentioning
confidence: 99%